PENGEMBANGAN LKPD BERBASIS EVERYDAY LIFE PHENOMENA PADA MATERI TERMOKIMIA UNTUK KELAS XI SMA/MA - Tri Handayani; Susilawati Susilawati; Sri Wilda Albeta (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this research was to develop the SWs based on everyday life phenomena in the thermochemistry topic. The research design in this development uses a research and development (R&D) and the ADDIE development framework which include analysis, design, development, implementation, and evalution. The reserch was conducted at University of Riau. The object of this reserch was the SWs based on everyday life phenomena in the thermochemistry topic. The data analysis technique used in this reserch was by calculating the percentage of validation values. The average score of SWs eligibility includes aspects of content feasibility, characteristics of everyday life phenomena, language, presentation and graphics with a successive percentage of 97.22%; 86.67%; 97.22%; 93.75%; 89.59% with all aspects in the valid/decent category. The percentage of user responses to the SWs developed was 85.4% by teachers and 92% by students with very good category.Key Words: Student Worksheet (SWs), Everyday Life Phenomena, and Thermochemistry.